2009
DOI: 10.1111/j.1442-2050.2009.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term outcome of fundoplication after lung transplantation

Abstract: Gastroesophageal reflux disease (GERD) in lung transplant recipients has gained increasing attention as a factor in allograft failure. There are few data on the impact of fundoplication on survival or lung function, and less on its effect on symptoms or quality of life. Patients undergoing fundoplication following lung transplantation from 1999 to 2005 were included in the study. Patient satisfaction, changes in GERD symptoms, and the presence of known side effects were assessed. The effect on lung function, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 20 publications
3
22
1
1
Order By: Relevance
“…Resolution of reflux symptoms as well as significant improvement in satisfaction with their condition was observed after antireflux procedures. These data support other authors findings [19,20]: Burton in 2009 found that after laparoscopic Toupet fundoplication in lung transplant patients 88% of the patients rated the surgery as excellent, Robertson et al noticed significant improvement in reflux symptoms index and gastrointestinal quality of life scores. However most of the studies evaluate short-term fundoplication effect.…”
Section: Discussionsupporting
confidence: 87%
“…Resolution of reflux symptoms as well as significant improvement in satisfaction with their condition was observed after antireflux procedures. These data support other authors findings [19,20]: Burton in 2009 found that after laparoscopic Toupet fundoplication in lung transplant patients 88% of the patients rated the surgery as excellent, Robertson et al noticed significant improvement in reflux symptoms index and gastrointestinal quality of life scores. However most of the studies evaluate short-term fundoplication effect.…”
Section: Discussionsupporting
confidence: 87%
“…Our study has comparable intra-operative data and no patients in our series have needed conversion to an open operation. No intra-operative or perioperative deaths have been reported by the Duke University group [5,23,24], although, recently, one post-fundoplication death has been reported [25]. We have experienced no mortality to date and no major complications were encountered.…”
Section: Discussionmentioning
confidence: 68%
“…Nissen fundoplication and Toupet fundoplication) can be performed safely on lung transplant candidates with advanced lung disease or lung transplant recipients with documented abnormal GOR [123,124,[127][128][129][132][133][134][135][136][137][138], thereby preventing reflux, aspiration of gastric secretions and related sequelae.…”
Section: Remarksmentioning
confidence: 99%